An alternative explanation for the reduced repeat-induced point mutation (RIP) efficiency in a gene-sized duplication in Neurospora crassa crosses heterozygous for a larger chromosome segment duplication - A Prakash (Fungal Genetics Reports, 2001)
Recently, it was reported that the efficiency of repeat-induced point mutation (RIP) in a gene-sized duplication was reduced in Neurospora crosses heterozygous for another larger segmental duplication (Bhat and Kasbekar 2001 Genetics 157: 1581-1590). Specifically, the authors showed that the frequency of RIP in the erg-3 gene due to a 1.3 kb duplication was reduced, if the chromosome segment duplications Dp(IIIR > [IR; IIR]) AR17, Dp(VIR>IIIR) OY329, or Dp(IVR > VII) S1229 were present in the same or the other parental nucleus of the premeiotic dikaryon. They have suggested that the larger segmental duplication acts as a sink and titrates the RIP machinery away from the smaller gene-sized duplication. However, there is an alternative and somewhat trivial explanation for their results.